(untitled) (Tzintzun, Revista de Estudios Históricos, 2020)
The article has the purpose of explaining the place that rural â€œnormalistaâ€ students, organized in the Federation of Farmworker Students of Mexico (FECSM), had in the corporate policy of the government of Lázaro Cárdenas (1934-1940), a little explored aspect of that government that was so decisive in Mexican political history of the twentieth century.